Training for Enhancement of Passing Grade Value of Job Seekers Registered at The Manpower Department of Jayapura City - Johanis R. Wanma; Yasir Attamimi (Ridwan Institute, 2022)
Jobs as a State Civil Apparatus (ASN) are still in demand by most job seekers throughout Indonesia and especially job seekers in Papua Province. Based on the Governor of Papua Letter Number: 800 / 4407 / Set regarding procurement, The 2018 general formation of civil servant candidates at the Papua provincial government held in the 2019 fiscal year stated that the Papua Provincial Government needed 606 formations with the distribution of 20% formation allocations for Non-Papuans and 80% formation allocations for Papuan poeple. Data from the Papua Province Regional Personnel Agency shows that there are 2896 applicants for prospective civil servants at the provincial level who have passed the administration and will then participate in the basic skills selection, which will be held in June 2019. This shows that job seekers' high interest in becoming Civil Apparatus The State (ASN) increased sharply until it reached almost 500% of the available formations (source: BKD Papua Province). The problem for the Papua Provincial Government is that the high interest has not been aligned with the ability to understand and do the Computer Assisted Test (CAT). By looking at the phenomenon in the field, especially for job seekers, it is necessary to have training related to the CAT Test for job seekers registered with the Jayapura City Manpower Office so that job seekers do not hesitate when taking the test. The training is divided into three stages. The stages first are the preparation after that, An introduction to the materials that will be followed when carrying out the Computer Assisted Test (CAT), and Tips and Tricks on how to do the questions quickly.